C-Kit Positive Cells from Failing Human Hearts: Role of Culturing Media on Cardiomyogenic Potentials - Anna Francesconi; Gaetano Paparella; Barbara Frossi; Elisa Del Terra; Francesco Saverio Ambesi Impiombato; Francesco Curcio (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2015)
Background: The possibility of culturing heart cells in order to regenerate damaged tissue is a challenging problem. Recent observations have demonstrated the possibility of isolating and expanding resident cardiac stem cells, which could favor regeneration and functional improvement of the myocardial tissue. Aims: To investigate two different culturing media: one promoting c-kit cells' growth and the other promoting differentiation in cardiac muscle cells. Methods: We obtained primary cultures from left ventricle myocardial tissues of 10 human hearts of patients with end-stage heart failure who received heart transplantation. Cells were first cultured in a medium containing high serum and low calcium/magnesium (Ca2+ /Mg2+) to promote cell growth (medium A). Than they were cultured in another medium that contained lower serum concentration and a variety of different factors in order to induce cell differentiation (medium B). The presence of c-kit, specific for stem cells, α-sarcomeric actin (SA), specific for skeletal and cardiac muscle cells, and α-smooth muscle actin (SMA), specific for smooth muscle cells was studied by immune-cytochemical analysis. Results: A high percentage of c-kit+, SMA-, SA- cells was observed in medium A; in medium B with lower serum and higher Ca2+/Mg2+ concentrations cells became c-kit-, AML+, SA+. In medium A, 78% of the cells were positive for c-kit. After culturing the same cell populations in medium B with lower serum and higher Ca2+ /Mg2+ concentrations, the percentage of c-kit positive cells decreased to 21% while the cells positive for SMA and for SA increased respectively from 28 to 82% and from 0 to 59%. Conclusions: Our results confirm the presence of a high percentage of c-kit positive cells in failing human myocardium and, for the first time, suggest a key role of calcium/magnesium concentration in promoting both c-kit cells' growth and their differentiation in human cardiac muscle.